The Hypothetic Model of Integrated Production-Based Learning with the 21st Century Learning Skills in Mechanical Engineering - Heri Yudiono; Pramono Pramono; Basyirun Basyirun (Jurnal Pendidikan Teknologi dan Kejuruan, 2019)
Vocational education building and development must consider the needs of the industry and the demands of 21st-century skills graduates. For these two requirements, it is necessary to innovate the learning model to improve the students’ learning experience and graduates’ performance. This study aims to develop a production-based learning model that is integrated with 21st-century learning skills to improve skills in mechanical engineering. The study employed focus group discussion and experts’ judgment. This study involved the mechanical engineering lecturers, the head of laboratory at the mechanical engineering department, the head of the department of mechanical engineering, the head of mechanical engineering vocational education, the head of the mechanical laboratory at the vocational schools, mechanical engineering teachers, vocational technology education experts, and curriculum specialists. The results show that the utility, feasibility, propriety, and accuracy of the production-based learning model integrated with 21st-century learning skills met the expected criteria and could be used to improve mechanical engineering skills.